How to successfully implement projects to improve the demand prediction process - Dittmann, J. Paul (Henry Stewart Talks, 2010)
Why initiatives fail, External factors affecting projects, Six special challenges with demand prediction projects, Four proven techniques to improve chances of success, Sustaining change is harder than the initial implementation, and a plan for it is needed, Getting full organizational buy-in is a huge challenge and should be prominent in the tasks of the project plan, Expectations must be managed, Communication must be focused on key individuals